Sifat Anatomi dan Sifat Fisis Kayu Teras Maesopsis eminii Engl.: The Anatomical and Physical Properties of the Heartwood of Maesopsis eminii Engl. - Dirna, Fitria Cita; Wahyuningtyas, Irma; Putri Hanifah, Nisrina (JURNAL HUTAN TROPIKA, 2025)
The anatomical and physically characteristics of wood are fundamental characteristics required to determine the quality of a wood species. This study aims to obtain information about the anatomical structure of wood and the physical properties of African heartwood (Maesopsis eminii Engl.). In this study, macroscopic and microscopic observations of wood were carried out, including color, radius, fiber length, fiber diameter, lumen diameter, cell wall thickness, and pore diameter, as well as the derived values ​​of fiber dimensions (felting power, runkle ratio, flexibility ratio, coefficient rigidity, and muhlsteph ratio). In addition, the physical properties studied were water content, density, specific gravity, and wood dimensional shrinkage (longitudinal, radial, and tangential). The results showed that African heartwood has a dark yellow to brownish color and has round to oval pores that are predominantly solitary with a mixed arrangement. Based on the derived values ​​of its fiber dimensions, African heartwood fibers are classified into strength class II. The physical properties of African